Pathology and Methodological Principles of Theoretical Medicine - Astrauskas, Vytautas (Problemos, 1977)
On the basis of extensive analysis of Soviet publications on the question, certain methodological problems of theoretical biology and theoretical medicine are discussed. The general and specific properties of the two sciences are revealed with particular emphasis on the social nature of man. Certain trends in genetization of medicine are forecasted.